2017
DOI: 10.18632/oncotarget.20477
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Chrysanthemum morifolium Ramat ameliorate colitis rats by modulating the intestinal microbiota community

Abstract: The gut microflora dysbiosis has been closely related with the inflammatory bowel disease (IBD). In this study, the effect of polysaccharides from Chrysanthemum morifolium Ramat on the gut microbiota was evaluated by ulcerative colitis (UC) rat model. Physiological and pathological analyses suggested that Chrysanthemum polysaccharides possessed notably protective effects on UC in vivo. Based on the Illumina MiSeq platform, 16S rRNA sequencing of the rat colonic contents indicated that the intestinal flora stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 64 publications
8
60
0
Order By: Relevance
“…LDA-LEfSe indicated that the TCCO-treated group exhibited a higher relative abundance of Erysipelotrichales and Rikenellaceae than did the SO-treated group. Tao et al [26] reported that an increase in the counts of Rikenellaceae provides enhanced intestinal protection. In addition, the SO-treated group exhibited a higher relative abundance in Prevotellaceae, and Darnaud et al [27] showed that DSS-treated REG3A-TG mice (which are less sensitive to colitis) exhibited a lower level of Prevotellaceae than did DSS-treated normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…LDA-LEfSe indicated that the TCCO-treated group exhibited a higher relative abundance of Erysipelotrichales and Rikenellaceae than did the SO-treated group. Tao et al [26] reported that an increase in the counts of Rikenellaceae provides enhanced intestinal protection. In addition, the SO-treated group exhibited a higher relative abundance in Prevotellaceae, and Darnaud et al [27] showed that DSS-treated REG3A-TG mice (which are less sensitive to colitis) exhibited a lower level of Prevotellaceae than did DSS-treated normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that gut microbiota appears critical in maintaining intestinal homeostasis and improving metabolism health. It is well known that intestinal flora dysbiosis is closely related to the development of various chronic diseases (Hand et al, 2016), such as metabolic syndrome (Chassaing et al, 2015), colorectal cancer (Wang et al, 2012), angiocardiopathy (Tang & Hazen, 2014), type II diabetes (Li et al, 2018a), adiposis (Chang et al, 2015), inflammatory bowel disease (Tao et al, 2017) and cancer (Ohtani et al, 2014). The occurrence of these diseases may be due to the damage of intestinal mucosal and decrease of bacteria abundance.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Chinese Pharmacopoeia, Flos Chrysanthemi could be mainly classified into five varieties 'Hangju', 'Boju', 'Chuju', 'Gongju' and 'Huaiju'. Many pharmacological studies reported that it possesses various functions of antioxidation [1][2][3], cardiovascular protection [4,5], antimicrobial [6] and anti-inflammatory [7,8], which are benefit from the mainly active components, like flavonoids. The variety the 'Hangju' of Flos Chrysanthemi, which has been cultivated for centuries and developed into several genotypes, and the genotype 'Zaoyang' has the largest cultivated area and yield among all the genotypes [9].…”
Section: Introductionmentioning
confidence: 99%